Motor development in children living within resource poor areas of the Western Cape - J. Jelsma; G. Ferguson (AOSIS, 2007)
Introduction: In 1986, Irwin-Carruthers tested 681 Black African babies from the Western Cape and concluded that the South African sample was in advance of the Denver sample both in fine and gross motor behaviour. This study was to determine whether the motor development of isiXhosa speaking children from the same area was still advanced compared to their North American counterparts. Method: The Bayley Scales of Infant Development-II were administered to 86 children attending well baby clinics, between the ages of 1-36 months. Results: The mean motor developmental quotient was 92 (SD=15). Twenty eight percent of the sample was either significantly or mildly delayed. No socio-economic or maternal characteristics were associated with this score. Conclusion: The reasons for the decrease in performance are not clear. The socio-economic situation of the mothers was poor and there were a large number of single mothers whose sole source of income was government child support grants.  It is likely that the cause of the decrease is multi-factorial. The mothers are clearly in need of emotional and financial support. It is suggested that the introduction of stimulation programmes might be useful in reducing the long term impact of this delayed development.